Business law - Marson, James (Oxford University Press, 2011)
This comprehensive textbook provides a thorough and accessible introduction to business law for the non-law student. Packed with up-to-date and relevant examples, it demonstrates the real applicability of the law to the business world, making it an invaluable companion for all those tackling business law for the first time. Whether you're a would-be entrepreneur or looking to a career in management, this book gives you the solid base you need to make confident business decisions in the future. Designed for non-lawyers, Business Law is written in a clear and easy-to-follow style which avoids exc.